Electrochemical method for the quantitative determination of Escherichia coli based on gold functionalized FTO substrate. Issue 6 (22nd February 2018) - Li, Pei; Wang, Xiaofang; Gao, Wenyu; Yan, Wei; Guan, Weijun; Ma, Yuehui; Yu, Yu; Ji, Fengmin; Wu, Songmei; Ding, Kejian
Abstract : This work presents a novel rapid and sensitive label-free electrochemical method for the detection of the antibacterial effect of surface nanostructures. Abstract : This work presents a novel rapid and sensitive label-free electrochemical method for the detection of bacteria on surface nanostructures. A simple electrochemical deposition and calcination method is employed to prepare different gold nanostructures on FTO substrate. The sensor based on nanostructure gold exhibits excellent linear relation between E. coli DH5α bacteria and the changes of Δ R ct, especially FTO-GEDC-D30, with a correction coefficient R 2 = 0.998. Both the spectrophotometric (OD600 methods) and fluorescence-staining methods also verified the reliability of electrochemical impedance spectroscopy (EIS) methods for evaluating the antibacterial activity of the gold nanostructure.